Streptococcus mutans in a Wild, Sucrose-Eating Rat Population - Coykendall, Alan L. (1974)
Streptococcus mutans, an organism implicated in dental caries and not previously found outside of man and certain laboratory animals, was isolated from the mouths of wild rats which ate sugar cane. The strains isolated fermented mannitol and sorbitol, and failed to grow in 6.5% NaCl or at 45 C. They formed in vitro plaques on nichrome wires when grown in sucrose broth. They also stored intracellular polysaccharide which could be catabolized by washed, resting cells. Deoxyribonucleic acid-deoxyribonucleic acid reassociations revealed two genetic types. One type shared extensive deoxyribonucleic acid base sequences with S. mutans strains HS6 and OMZ61, two members of a genetic type found in man and laboratory hamsters. The other type seemed unrelated to any S. mutans genetic type previously encountered. It is concluded that the ecological triad of tooth-sucrose-S. mutans is not a phenomenon unique to man and experimental animals.